2016
DOI: 10.1007/s10876-016-1128-2
|View full text |Cite
|
Sign up to set email alerts
|

Flower-Like Copper Sulfide Nanocrystals are Highly Effective Against Chloroquine-Resistant Plasmodium falciparum and the Malaria Vector Anopheles stephensi

Abstract: Anopheles stephensi is a mosquito of outstanding public health relevance, acting as a major vector of malaria in a number of tropical and subtropical areas worldwide. In recent years, important efforts have been conducted to propose nano-formulated larvicides as valuable alternatives to synthetic insecticides currently marketed. In the present study, the toxicity of flower-like copper sulfide (CuS) nanocrystals has been investigated on the malaria vector A. stephensi and Plasmodium parasites. Characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…3 ). After 4 days of 4,7-dichloroquinoline treated groups exhibited the percentage of parasitemia 10.6 ± 0.8% at 300 mg/kg/day than that of the control drug chloroquine (CQ) 1.0 ± 0.0% 37 , 66 . Tang et al 67 showed antimalarial activities against the P. falciparum strain K173 with EC 50 values ranging from 0.38 to 0.43 mg/kg.…”
Section: Resultsmentioning
confidence: 94%
“…3 ). After 4 days of 4,7-dichloroquinoline treated groups exhibited the percentage of parasitemia 10.6 ± 0.8% at 300 mg/kg/day than that of the control drug chloroquine (CQ) 1.0 ± 0.0% 37 , 66 . Tang et al 67 showed antimalarial activities against the P. falciparum strain K173 with EC 50 values ranging from 0.38 to 0.43 mg/kg.…”
Section: Resultsmentioning
confidence: 94%
“…Nanotechnology has shown promise in creating insecticides with less environmental impact to bridge this gap [20][21][22][23]. The medical and veterinary sciences [24] and entomology [25] are only two examples of the many areas of study that have benefited from nano-technology in recent years. Nano-pesticides have the potential to encompass a wide variety of pesticide formulations that have proven helpful as carriers of potent pesticides over the past decade [26].…”
Section: Introductionmentioning
confidence: 99%